Mercantilización de los servicios de salud para el desarrollo: el caso de Colombia Commodification of health care services for development: the case of Colombia - Oscar Echeverri (Pan American Health Organization, 2008)
This is a succinct analysis of the circular relationship between health and development and the changes occurring over recent decades regarding health care services production and delivery that have resulted in a new paradigm. From the late 1970s through the 1980s, three major, worldwide shifts occurred that changed health care services in Colombia and in other Latin American countries: the privatization of government entities, the commodification of health care services, and the failure of the Soviet model. Health care system reform in Colombia, considered by some experts to be a model, is an example of health care commodification that, 15 years later, has not achieved the coverage, nor the equity, nor the efficiency, nor the quality, that it should have. More so than the market, the problem has been with the market entities that seek disproportionate profits. A solution for this situation is to appeal to nonprofit organizations for the purchase and sale of health care services.